From numbers to life savers, silent heroes in town - Zakaria, Ros Amalina (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2024)
In the midst of a busy town, hidden in a corner of the local government building, is a little but powerful office. Here, in the accountant's office, experts work away in silence. Though this accountant's work may seem mundane and unimportant to those outside, they are actually responsible for a great deal of the community's well-being. Imagine this - Danial, a young accountant in his early thirties, sits at his desk, surrounded by mountains of paperwork. The town's finances are shown on his computer screen, blazing with statistics and graphs. Danial often reflects on the ways in which his job influences others in his surroundings. Whether it's for fixing a damaged road, paying trash collectors, or keeping parks clean for kids to play in, he knows that every Ringgit he allocates is helping someone. Every year, Danial will sit down in a meeting with the mayor and the head of other departments to plan for next year’s budget. “What do you think is most important next year?” he would ask. “More funds for public safety?” or “What about improving the Public Hall for the community? Danial's sense of responsibility intensifies as he recognises that the decisions they make will have a ripple effect on the lives of all the town’s residents. One day, as Danial reviewed the finances, he noticed something troubling – the town was running over budget for the emergency services department. Without a second thought, he called for an emergency meeting. “We need to be careful,” he said, looking at his colleagues. “If we’re not vigilant, we risk not being able to support our solid waste management department, which keeps our town clean.” They brainstormed ideas and worked late into the night, finding ways to cut unnecessary expenses while still ensuring that the cleaning workers had the equipment they needed to keep the town clean and free from litter and pollution. Throughout the year, Danial’s team received several grants from State and Federal Government to fund projects in his district. These grants aim to improve the infrastructure like roads and drainage system, landscaping and to provide facility to help small businesses. These mean a lot to the community and Danial feels so proud to be a part of it. He realizes that every paperwork and figures he worked with could bring a favourable future for the local people.